1986
DOI: 10.1083/jcb.103.6.2683
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface proteoglycan associates with the cytoskeleton at the basolateral cell surface of mouse mammary epithelial cells.

Abstract: The cell surface proteoglycan on normal murine mammary gland mouse mammary epithelial cells consists of an ectodomain bearing heparan and chondroitin sulfate chains and a lipophilic domain that is presumed to be intercalated into the plasma membrane. Because the ectodomain binds to matrix components produced by stromal cells with specificity and high affinity, we have proposed that the cell surface proteoglycan is a matrix receptor that binds epithelial cells to their underlying basement membrane. We now show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
185
1
3

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(200 citation statements)
references
References 47 publications
11
185
1
3
Order By: Relevance
“…Among epithelial cell types, the distribution of staining on the plasma membrane ranges from staining over the entire cell surface (squamous epithelia, such as cornea and tongue) to staining of only the basolateral surface (cuboidal and columnar epithelia, such as mammary duct and trachea) [40]. An analysis of syndecan-1 distribution on the surface of cultured mammary epithelial cells revealed that, in newly plated cultures, the proteoglycan is present initially over the entire cell surface, but becomes restricted to the basolateral surface as the cells become polarized [71].…”
Section: Membrane Localization Of Syndecansmentioning
confidence: 99%
See 2 more Smart Citations
“…Among epithelial cell types, the distribution of staining on the plasma membrane ranges from staining over the entire cell surface (squamous epithelia, such as cornea and tongue) to staining of only the basolateral surface (cuboidal and columnar epithelia, such as mammary duct and trachea) [40]. An analysis of syndecan-1 distribution on the surface of cultured mammary epithelial cells revealed that, in newly plated cultures, the proteoglycan is present initially over the entire cell surface, but becomes restricted to the basolateral surface as the cells become polarized [71].…”
Section: Membrane Localization Of Syndecansmentioning
confidence: 99%
“…There is evidence suggesting a role for syndecan binding to the actin cytoskeleton in this process, perhaps triggered by extracellular-matrix-dependent cross-linking of syndecan molecules on the cell surface [71]. Such a mechanism would indicate a role for the cytoplasmic domain of syndecan-1 in targeting of the proteoglycan in polarized epithelial cells.…”
Section: Membrane Localization Of Syndecansmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibronectin contains a heparinbinding domain and has been found to interact with syndecan-4 and glypican-1 (12). Therefore, HSPG have been proposed to function as receptors for anchoring heparin-binding ECM proteins, like fibronectin, to endothelial cells (13,14). Recently fibronectin has also been shown to bind VEGF, suggesting an additional role for this ECM protein in the storage of VEGF (15).…”
mentioning
confidence: 99%
“…HSPGs are members of a family of cell surface proteins with polysaccharide side chains characterized by alternating uronic acid and glucosamine units (12,13). They occur as either integral membrane (14,15) or as secreted extracellular matrix proteins (12). The polysaccharide chains are connected to the core proteins through serine of the Ser-Gly (SG) consensus sequence whereby the presence of nearby acidic amino acids and the repetition of SGs are factors that promote attachment of glycosaminoglycan (GAG) side chains and favor synthesis of heparan sulfate (HS) over chondroitin sulfate (CS) side chains (16,17).…”
mentioning
confidence: 99%